Facilitation of glutamate and GABA release by P2X receptor activation in supraoptic neurons from freshly isolated rat brain slices - Vavra, V; Bhattacharya, A; Zemkova, H (Neuroscience, 2011)
The supraoptic nuclei (SON), the hypothalamic release site of vasopressin and oxytocin, receive a non-glutamatergic, excitatory input from the caudal medulla that uses noradrenaline and ATP as neurotransmitters. Here, we studied the actions of extracellular ATP on SON neurons in hypothalamic slices isolated from the brains of 16- to 24-day-old rats. Whole-cell current clamp recordings performed 1-6 h after isolation showed that exogenous ATP application increased the frequency of action potentials and induced the depolarization of resting membranes. Voltage clamp recordings showed that ATP increased the frequency of GABAergic or glutamatergic spontaneous synaptic currents without changing their amplitude and evoked inward current (126±13 pA) in about 80% of SON neurons. The application of ATPγS and 2MeSATP mimicked the effects of ATP, but 2MeSADP, 2MeSAMP and αβmeATP had no effect. The P2X7 receptor agonist, BzATP, did not induce an inward current, but it increased intracellular calcium concentration in non-neuronal SON cells in slices. Suramin and pyridoxalphosphate-6-azophenyl-2',4'-disulfonic acid (PPADS) inhibited ATP-induced currents, whereas pH 6.5 and ivermectin, a specific allosteric modulator of the P2X4 receptor, potentiated ATP-induced currents. The P2Y1-selective antagonist, 2'-deoxy-N⁶-methyladenosine 3',5'-bisphosphate tetrasodium salt (MRS 2179), had no effect on ATP-induced responses. Quantitative real-time PCR showed that P2X2>P2X7>P2X4 purinergic receptor mRNAs were expressed in the SON tissue, but the levels of P2X1, P2X3, P2X5, P2X6, P2Y1, P2Y2 and P2Y12 mRNA were minor. These results show that SON neurons express functional presynaptic and extrasynaptic P2X2 and P2X4 receptors that modulate glutamate and GABA release and control the electrical excitability of SON neurons.
Keywords: Patch-Clamp Techniques; adenosintrifosfát; Rats, Wistar; orgánové kultury - kultivační techniky; GABA; metoda terčíkového zámku; potkani Wistar; Organ Culture Techniques; polymerázová řetězová reakce s reverzní transkripcí; neurony; krysa rodu Rattus; Glutamic Acid; nucleus supraopticus; Animals; Receptors, Purinergic P2X2; akční potenciály; Action Potentials; purinergní receptory P2X2; zvířata; Neurons; Supraoptic Nucleus; Rats; Reverse Transcriptase Polymerase Chain Reaction; Adenosine Triphosphate; kyselina glutamová; gamma-Aminobutyric Acid